Cancer Stem Cells and Signaling Pathways in Colorectal Cancer - Rustam Effendi YS; Imelda Rey (The Indonesian Society for Digestive Endoscopy, 2018)
Colorectal cancer (CRC) is the third most common cancer in males, the second in females and is the second leading cause of cancer related death worldwide. Despite recent advances in chemotherapy, and targeted therapy for CRC, the prognosis for patients with advanced cancer has remained poor, due to drug resistance, metastasis and recurrence. A small fraction of cells possess tumor propagation abilities. These are termed “cancer stemcells (CSCs). A subset of colorectal cancer stem cells, may hold a key to controlling cancer. The cancer stem cell (CSC) model suggests that tumors are hierarchically organized, only CSCs possess cancer-promotingpotential. The killing of CSCs is thought to be a critical component of effective antitumor therapies. A number of signaling pathways, most notably the Wingless related (Wnt), transforming growth factor-beta (TGF-β), Notch and Hedgehog signaling and other mechanisms have been found to be associated with CSCs in CRC. They play important roles in maintaining the growth and functional integrity of CSC. Many new molecules are now being studied to block theses pathways. Some of the molecules block the self-renewal and induction of apoptosis in CSCs. The design of CSC-targeted interventions is a rational target, and reduce local recurrenceand metastasis. This review aims to summarize the issue on CSCs and signaling pathway relevant for CRC, which may lead to more effective therapeutic strategies for CRC.